PENGARUH e-LKPD BERBANTUAN WEBSITE WIZER.ME BERBASIS MODEL INQUIRY BASED LEARNING (IBL) TERHADAP HASIL BELAJAR KOGNITIF DAN SIKAP DEMOKRATIS PESERTA DIDIK KELAS III SEKOLAH DASAR - Emisda Noprianti; Osa Juarsa; Neza Agusdianita (STKIP Subang, 2026)
This study was motivated by the low cognitive learning outcomes and democratic attitudes of third-grade elementary school students in Pancasila Education, particularly on the topic of rights and obligations. Teacher-centered learning and the use of conventional worksheets caused students to be less active and less able to understand the application of rights and obligations in daily life. This study aimed to determine the effect of e-LKPD assisted by the Wizer.Me website based on the Inquiry Based Learning (IBL) model on students’ cognitive learning outcomes and democratic attitudes, as well as the relationship between both variables. The study used a quantitative approach with a quasi-experimental method and The Matching-Only Pretest-Posttest Control Group Design. Samples were selected using cluster random sampling consisting of an experimental class and a control class. Data were collected through cognitive learning outcome tests and democratic attitude questionnaires. The results showed that the use of e-LKPD based on Inquiry Based Learning (IBL) significantly improved students’ cognitive learning outcomes, with an N-Gain score of 0.58 in the experimental class, higher than 0.23 in the control class. In terms of democratic attitudes, the experimental class achieved an N-Gain score of 0.52, while the control class obtained 0.20. Furthermore, there was a positive and significant relationship between cognitive learning outcomes and democratic attitudes, with a Pearson correlation value of 0.476 and a significance value of 0.002 < 0.05. Therefore, e-LKPD assisted by Wizer.Me based on Inquiry Based Learning (IBL) was effective in improving students’ cognitive learning outcomes and democratic attitudes.